Assessing lake-destination image: insights from the industry side. Issue 1 (6th March 2017) - Rodrigues, Ana Isabel; Correia, Antónia; Kozak, Metin
Abstract : Purpose: The literature review reveals that lake tourism and lake-destination areas (LDA) have been particularly absent from destination image (DI) studies over 45 years of research. In fact, there is a lack of research concerning the characteristics of lake tourism, particularly related to the attributes involved in the formation of lake-DI. Therefore, this paper aims to explore lake tourism and lake-DI based on the Alqueva Lake more thoroughly, it being the biggest man-made lake in Europe, as an emerging lake-destination area located in the south of Portugal. Design/methodology/approach: Within this, the perceptions of stakeholders professionally involved with this type of destination were examined through 17 semi-structured interviews based on content-analysis as a qualitative technique. Framed by the important contribution of visual-based research in tourism studies, this study adopts two approaches: an attribute-based approach (textual data) and a photo-based approach (visual data), to strengthen the concept, characteristics and dimensions of lake tourism and image attributes applied to this type of destinations. Multiple techniques of extracting data were used, demonstrating the importance of using various techniques in obtaining image attributes as a first step in assessing DIs. Findings: The findings revealed textual and pictorial attributes related to lake tourism and LDA, which confirms that although image attributes are universally important, depicting specific attributes is important considering particular types of tourism, such as lake tourism. Originality/value: This is a very recent sub-field of DI studies, which justifies its investigation on a theoretical as well as on a practical management level.